A meta-analysis of re-treatment for intravenous immunoglobulin-resistant Kawasaki disease. (19th January 2015) - Yang, Xi; Liu, Guiying; Huang, Yaqian; Chen, Stella; Du, Junbao; Jin, Hongfang
Abstract: Objective: To determine the optimal drug therapy for intravenous immunoglobulin-resistant Kawasaki disease. Methods: Studies regarding drug therapy for intravenous immunoglobulin-resistant Kawasaki disease were selected from medical electronic databases including PubMed, Medline, Elsevier, and Springer Link. The effectiveness in terms of temperature recovery and coronary artery damage was compared between a second intravenous immunoglobulin treatment and glucocorticosteroid treatment for children with intravenous immunoglobulin-resistant Kawasaki disease using meta-analysis with Review Manager 5.3 software. Indices to evaluate the effects were body temperature, biomarker levels, and coronary artery lesions detected by echocardiography. Results are reported as relative risks or odds ratio with a 95% confidence interval and p<0.05. Results: Meta-analysis included 52 patients in the second intravenous immunoglobulin treatment group and 75 patients in the glucocorticosteroid treatment control group from four studies that met our inclusion criteria. Temperatures of patients who received glucocorticosteroid treatment were effectively controlled compared with those who received a second intravenous immunoglobulin treatment (relative risk=0.73, 95% confidence interval: 0.58–0.92, p=0.007). There were no differences, however, in the incidence of coronary artery lesions between the two groups (odds ratio=1.55, 95% confidence interval: 0.57–4.20, p=0.39). Conclusions: Glucocorticosteroids are more effective in controlling body temperature compared with intravenous immunoglobulin re-treatment in intravenous immunoglobulin-resistant Kawasaki disease children; however, glucocorticosteroids and intravenous immunoglobulin re-treatment showed no difference in the prevention of coronary artery lesions.